Identification of Staphylococcus aureus Cellular Pathways Affected by the Stilbenoid Lead Drug SK-03-92 Using a Microarray - William R. Schwan; Rebecca Polanowski; Paul M. Dunman; Sara Medina-Bielski; Michelle Lane; Marc Rott; Lauren Lipker; Amy Wescott; Aaron Monte; James M. Cook; Douglas D. Baumann; V.V.N. Phani Babu Tiruveedhula; et al. (MDPI AG, 2017)
The mechanism of action for a new lead stilbene compound coded SK-03-92 with bactericidal activity against methicillin-resistant Staphylococcus aureus (MRSA) is unknown. To gain insight into the killing process, transcriptional profiling was performed on SK-03-92 treated vs. untreated S. aureus. Fourteen genes were upregulated and 38 genes downregulated by SK-03-92 treatment. Genes involved in sortase A production, protein metabolism, and transcriptional regulation were upregulated, whereas genes encoding transporters, purine synthesis proteins, and a putative two-component system (SACOL2360 (MW2284) and SACOL2361 (MW2285)) were downregulated by SK-03-92 treatment. Quantitative real-time polymerase chain reaction analyses validated upregulation of srtA and tdk as well as downregulation of the MW2284/MW2285 and purine biosynthesis genes in the drug-treated population. A quantitative real-time polymerase chain reaction analysis of MW2284 and MW2285 mutants compared to wild-type cells demonstrated that the srtA gene was upregulated by both putative two-component regulatory gene mutants compared to the wild-type strain. Using a transcription profiling technique, we have identified several cellular pathways regulated by SK-03-92 treatment, including a putative two-component system that may regulate srtA and other genes that could be tied to the SK-03-92 mechanism of action, biofilm formation, and drug persisters.